Should public opinion affect our individuality? - Lyman, Mary Eliza (My University, 1894)
Introduction: “Opinion” says Sir Thos. Brown, “rides upon the neck o reason; and men are happy, wise or learned according as that empress shall set them down in the register of reputation. However, weigh not thyself in the scales of thy own judgment but let the opinion of the judicious be the standard of thy merit.” This is a question that comes before us in every relation of life, and it is always within our own choosing whether or not we will do certain things that are according to or against “public opinion.” It has been truly said that “men may encounter without fear the danger of the sea, the horrors of war, the pestilence that walketh at Monday, but the opinion of all men he cannot face so easily, and why? Because the desire to be well thought of by others is one of the most deepseated of all sentiments that belongs to the human heart.” We are by nature imitative creatures, fearing to do a single uncommon thing, for the reason that it might make us ridiculously conspicuous and if perchance we do reject the popular standards, it is generally thought that all standards are rejected. Boldness, therefore on our part is frequently very essential, in order that the wrong might be righted. This determining the right or wrong of a popular sentiment is very hard sometimes for says Bishop Wilkins “Time wears out the fiction of opinion and doth by degrees discover and unmask that fallacy ungrounded persuasions and confirms the dictates and sentiments of nature”.
Citation: Lyman, Mary Eliza. Should public opinion affect our individuality?. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Opinion; Public; Peer pressure; Individualism; Philosophy; Sociology; Theses; Manuscripts (documents)